XRD as an Alternative Technique for Cation Distribution Characterization of MFe2O4 Magnetic Nanoparticles - Michel Fernando Montañez Molina; Franklin David Muñoz Muñoz; Ana Karina Cuentas Gallegos; David Alejandro Dominguez Vargas; Jose Trinidad Elizalde Galindo; Gerardo Soto Herrera; Hugo Tiznado; Mario H. Farias; Javier Alonso Lopez Medina (Journal of Nanotechnology)
This work focuses on utilizing the X-ray diffraction technique as an alternative method to specialized and high-cost techniques such as X-ray photoelectron spectroscopy to obtain the cation distribution in magnetic nanoparticles as MFe2O4 with spinel structure synthesized by thermal decomposition. X-ray diffraction measurements for MFe2O4 with M = Co2+ as transition cation (inverse spinel CoFe2O4) showed sensitivity to the cation distribution for octahedral and tetrahedral sites in this material with this kind of crystalline structure, being a good option for its determination. The cation distribution was obtained from the X-ray diffraction intensity ratios for the most sensitive crystalline planes to the cations in octahedral and tetrahedral sites. Besides, the Debye–Scherrer equation and line profile analysis method from the diffraction pattern were used to determine the size distribution and the crystallite size. The size distribution obtained by X-ray diffraction was from 15 to 18 nm, while transmission electron microscopy was found to be from 10 to 25 nm. The inversion degree x derived from X-ray diffraction exhibits variability within the interval 0.6 < x < 0.8, not very far from that obtained by X-ray photoelectron spectroscopy (x = 0.67). This material exhibits a saturation magnetization of 124.88 emu g−1. Consequently, the X-ray diffraction technique opens the possibility of obtaining reliable information related to nanoparticles’ morphological and chemical properties with spinel structure.